Pacification and Reconciliation in the Spanish Habsburg Worlds (Brepols, 2026)
This is the first volume to analyze pacification strategies within the Spanish Monarchy on a global level. It deals with the development and aftermath of the many early modern revolts on the Iberian and Italian Peninsula, the Sicilian and Sardinian islands, the cities along the North Sea and the Spanish Americas. These comparative studies uncover the different ways in which the Spanish Monarchy dealt with rebellion from cities and constituencies, ranging from military responses and repression to offers for negotiation and reconciliation. They also point out common characteristics of these pacification processes, such as the promises of pardon, the granting of grace and the instruction of peace envoys. The different chapters, each accompanied by an edition of sources, show how the reconciliation and reincorporation into the Spanish Habsburg orbit proved to be a painstaking process with an unpredictable outcome.